On the modelling of dynamic problems for biperiodically stiffened cylindrical shells = Modelowanie zagadnień dynamiki w biperiodycznie użebrowanych powłokach walcowych - Tomczyk, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Thin linear-elastic cylindrical shells having a micro-periodic structure along two directions tangent to the shell midsurface (biperiodic shells) are objects of considerations. The aim of this contribution is to formulate a new mathematical nonasymptotic model for the analysis of dynamic problems for such shells.
Keywords: powłoki walcowe typu Kirchhoffa-Love'a; powłoki periodycznie użebrowane; powłoki gęsto użebrowane; dynamika; modelowanie; biperiodic cylindrical shells; dynamics; mathematical modelling; averaging of integral functionals; lenght-scale effect